La leadership di Matteo Renzi. Il leader “televisivo” alla prova delle primarie del Partito democratico - Damiani, Marco; Mazzoni, Marco (SocietàMutamentoPolitica, 2017)
The following article aims to study the 2013 primaries organized by the PD (Partito Democratico) for the election of the National Secretary of the Party. The outcome of said primaries (leader selection), that sees Matteo Renzi as the winner only a few weeks before his appointment to the presidency of the Council of Ministers, is compared to that obtained by the same party in 2007 and in 2009, respectively with Veltroni and Bersani as Secretaries. In this specific case study, the paper aims to analyse the peculiarities that distinguish Renzi’s leadership from that exercised by his predecessors. Within this framework our objective is to comprehend the role played by the mass media, and how Renzi used it in the internal battle for the party’s Secretariat. Our interest lies in understanding whether (and eventually why) television has been the informative tool most used by the people that, in the 2013 primaries, voted for Renzi. The results of our research, conducted using data provided by C&LS (Candidate & Leader Selection - www.cals.it), Standing Group of the Societá Italiana di Scienza Politica, highlight a close correlation between the candidate of choice and the communication tool used to access information regarding the primaries.